2013
DOI: 10.7863/ultra.32.5.771
|View full text |Cite
|
Sign up to set email alerts
|

Sonographically Guided Patellar Tendon Fenestration: Prognostic Value of Preprocedure Sonographic Findings

Abstract: The presence of a well-defined area of tendinosis on sonography was associated with clinical improvement after percutaneous sonographically guided fenestration of the patellar tendon. All tendons either improved (76%) or showed no change (24%) in the functional pain score at 4 weeks after fenestration.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
14
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(15 citation statements)
references
References 26 publications
(29 reference statements)
1
14
0
Order By: Relevance
“…To date, the predictive value of sonography after needle tenotomy in elbow epicondylopathies has not been explored. However, in the patellar tendon, clinical outcomes were improved in tendons with well‐defined areas of tendinosis compared with tendons with ill‐defined areas 4 weeks after tenotomy …”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…To date, the predictive value of sonography after needle tenotomy in elbow epicondylopathies has not been explored. However, in the patellar tendon, clinical outcomes were improved in tendons with well‐defined areas of tendinosis compared with tendons with ill‐defined areas 4 weeks after tenotomy …”
Section: Discussionmentioning
confidence: 98%
“…However, there is some confusion regarding the procedure and associated terminology. In general, tenotomy, fenestrations and needling are considered synonymous and described as 20‐50 needle‐passes through the tendon . Going deeper, other authors described two different needle tenotomy modalities, including the so‐called peppering technique, which involves less tendon fenestrations (approximately five needle passes), and a more aggressive needle tenotomy involving multiple abrasions until tissue softening.…”
Section: Discussionmentioning
confidence: 99%
“…Although studies have shown patient improvement after ultrasound-guided tendon fenestration, there are only limited studies evaluating fenestration of gluteal tendons, and there are no studies comparing gluteal tendon fenestration to other tendon treatments such as PRP injection. [9][10][11][12][13][19][20][21] Although a comprehensive review of PRP treatment is beyond the scope of this discussion and has previously been described in the literature, PRP involves centrifuging autologous venous blood to separate the platelet-rich layer, which can then be injected into an abnormal tendon to promote healing. 14,22,23 Similar to tendon fenestration but in a higher concentration, growth factors are released from α granules in platelets to promote tendon healing.…”
Section: Discussionmentioning
confidence: 99%
“…Ultrasound-guided percutaneous needle fenestration (or tenotomy) has been used to effectively treat underlying tendinosis and tendon tears, including tendons about the hip and pelvis. [9][10][11][12][13] The rationale behind tendon fenestration is that a chronic degenerative tendon process is converted to an acute process, and inherent growth factors are introduced with bleeding, thereby promoting tendon healing. 10 Similarly, autologous platelet-rich plasma (PRP), often combined with tendon fenestration, has been used throughout the body to treat tendinosis and tendon tears, as injection into a tendon promotes healing via the introduction of growth factors concentrated in and released from platelets.…”
mentioning
confidence: 99%
“…With respect to sclerosing treatments, immunohistochemical analyses of tendon biopsies from hypervascular regions have shown nerves located close to blood vessels, which is possibly why ultrasoundguided sclerosing treatments have been effective (17 -20). In addition, treatment by ultrasound-guided patellar tendon fenestration or arthroscopic shaving has also been reported (17,18,21).…”
Section: State-of-the-art Ultrasonographic Findings In Lower Extremitmentioning
confidence: 99%